IMPROVING STUDENTS’ ABILITY IN TRANSLATING INDONESIAN FOLKLORES INTO ENGLISH USING CAT TOOLS - A.A. Istri Yudhi Pramawati; Ni Made Sukma Dewi; Nengah Ziva Titania Aricadia (Bajang Institute, 2023)
This research aims at describing students translation ability in translating Indonesia folklores into English through classroom action research. This research was conducted on the sixth semester students in Facultylation quality of Teacher Training, Universitas Mahasaraswati Denpasar. The data was analyzed by using descriptive qualitative. Based on the result of the analysis, it showed that students’s translation quality was improved. It could be seen from the naturalness and the consistency use of English terms. Besides, students’ translation products greatly improved, with the average progress score rising to 12.55 and they also showed positive response to the use of CAT Tools.